Black political organizations in the post-civil rights era - Johnson, Ollie A., 1962-; Stanford, Karin L., 1961- (Rutgers University Press, 2002)
We know a great deal about civil rights organizations during the 1960s, but relatively little about black political organizations since that decade. Questions of focus, accountability, structure, and relevance have surrounded these groups since the modern Civil Rights Movement ended in 1968. Political scientists Ollie A. Johnson III and Karin L. Stanford have assembled a group of scholars who examine the leadership, membership, structure, goals, ideology, activities, accountability, and impact of contemporary black political organizations and their leaders. Questions considered are: How have t.